(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
José Elguero Videgaray, from Michoacán, was one of the most renowned Mexican writers, journalists, and Hispanists of the first half of the 20th century. A fervent Catholic and lover of History, Elguero was a great admirer of New Spain’s colonial past to the extent that few like him devoted themselves to the defense of the Spanish heritage in Mexico, as well as to the recognition of its strategic value for the revitalization of Mexican national identity, particularly in the face of the powerful influence of the United States or the emergence of new ideologies such as Soviet communism. The article studies the trajectory and work of this journalist from Michoacán and analyzes the arguments that led him to defend the Spanish heritage in Mexico against the Hispanophobia of those he would call the “false apostles”.